2020
DOI: 10.1149/1945-7111/abb176
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Sensor for Monitoring the Alumina Dissolution and Concentration in a Cryolite-Alumina Melt

Abstract: The alumina dissolution in a cryolite-alumina melt was studied by voltammetry using a new design of the electrochemical sensor. It consisted of a working carbon electrode, shielded with a pyrolytic boron nitride tube, and the counter electrode, forming an alloy with aluminum, with a developed surface. The difference of such electrochemical measuring devices from the known designs is the use of a copper counter electrode (cathode), which forms an alloy with the deposited aluminum. It allows excluding the measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…All the measurements indicate an increase in the peak current with increasing oxide concentration until saturation is reached, just as observed during investigations involving alumina in cryolitic electrolyte systems [8,10,11,13]. It can thus be concluded that the REOs behave similarly to alumina in their corresponding fluoride electrolytes.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…All the measurements indicate an increase in the peak current with increasing oxide concentration until saturation is reached, just as observed during investigations involving alumina in cryolitic electrolyte systems [8,10,11,13]. It can thus be concluded that the REOs behave similarly to alumina in their corresponding fluoride electrolytes.…”
Section: Discussionsupporting
confidence: 79%
“…Investigations involving electrolytes for aluminium production have shown that the peak current prior to the passive layer formation increases with increasing oxide concentration [8,10,11,13]. Thus, it is possible to correlate the concentration of the dissolved oxide species with the observed peak current.…”
Section: Introductionmentioning
confidence: 99%
“…The disadvantage of such methods is the difficulty of the results' interpretation, especially if the system under study contains several impurity elements with similar electrochemical characteristics. Nevertheless, the electrochemical procedures using sensors for the determination of the content of elements in molten electrolytes are rather widely represented [19,[21][22][23]. Wang et al [24] used voltammetry to determine the oxygen content (in concentration limits of 200-1000 ppm) in FLINaK containing different amounts of Li 2 O. Voltammograms were obtained on spectrally pure graphite with a potential sweep rate of 0.05 V/s.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Manning et al [25] only managed to obtain voltammograms with a clear anodic peak for LiF-NaF-KF and LiF-BeF 2 melts with a gold working electrode. On the other hand, the possible influence of the cathode process on the CV dependencies was noted in [22].…”
Section: Introductionmentioning
confidence: 99%